IDENTIFICATION OF A HOTEL BUILDING ENERGY CONSERVATION OPPORTUNITIES IN BANDUNG - Dwisstya Utami, Amanda
Hotel is one of an example of commercial buildings with high energy consumption which caused by the customer’s demand of good service and comfort while using the facility. Hence, this study is conducted to identify Energy Conservation Opportunity (ECO) in a 4-star hotel building in Bandung to improve the building energy performance. Evaluating EUI (Energy Use Intensity) is done to achieve the objective. The lower EUI values, shows the better energy building performance. Evaluation of EUI value is done by simulation using Energyplus V8.4 software. The result shows that the building actual condition has EUI value of 252,20 kWh/m2/year with the condition of temperature setpoint often not met. The desired temperature setpoint is 19ºC while the room temperature shows higher temperature. There are several parameters changed such as SC glass, temperature setpoint, and doubled chiller capacity. The result shows that the most effective energy saving method attained when chiller capacity increased and temperature setpoint set higher. When the entire hotel area are set at setpoint temperature 25ºC, the EUI value falls down as much as 21,43% (48 kWh/m2/tahun) and when the setpoint temperature 25ºC set at the public area, EUI value drops 9,19% (21 kWh/m2/year) Using bigger chiller capacity, the setpoint temperature at public area often met unlike using one chiller only.